Theben-West, Ägypten: Die Memnon-Kolosse und der Totentempel Amenophis’ III. auf dem Kom el-Hettan - Sourouzian, Hourig (e-Forschungsberichte des DAI, 2023)
Since 1998 restoration and conservation work of the temple of Amenophis III had been conducted. During the campaign in 2012, main tasks included the restoration of the colossus of Amenhotep III north of the passage to the 2nd pylon, rearranging parts or the royal alabaster colossus of the 3rd pylon and further restoration works in the peristyle. Additionally, in 2013 the project was entrusted by the Ministry of State for Antiquities with an Emergency Salvage Project on two colossi of Amenhotep III at the northern gate of his temple, co-directed by M. Abd el-Maqsoud and the Gurna Inspectorate, to save them from damage done by irrigating water, to excavate the area and to prepare the statues for their re-erection.